Clinical Simulation in the Training of Obstetrics and Gynecology Resident from the Perspective of Medical Residency Programs - Vidotti, Simone Pereira; Batista, Nildo Alves (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective This study analyzes the role of clinical simulation in internal medical residency programs (IMRP) in Obstetrics and Gynecology (OB/GYN), attributed by the supervisors, in the training of residents in the city of São Paulo (SP).Methods Cross-sectional descriptive, qualitative, and exploratory approach. Semi-structured interviews were performed with ten supervisors of Medical Residency programs in Obstetrics and Gynecology. Interviews were analyzed by means of content analysis under the thematic modality, starting with the core the role of clinical simulation in Obstetrics and Gynecology Medical Residency Programs.Results Supervisors view Clinical simulation as: a complementary tool for the teaching and learning process, a possibility of a safe teaching and learning environment, an opportunity to learn from mistakes, a support for professional practice committed to patient safety, a learning scenario for teamwork, a scenario for reflection on the work process in Obstetrics and Gynecology, a scenario for evaluative processes in the medical residency. Still according to supervisors, Clinical Simulation favors decision-making and encourages the resident participation in activities.Conclusion Supervisors recognize Clinical Simulation as a powerful pedagogical tool in the learning process of resident doctors in Obstetrics and Gynecology Residency Programs.
Keywords: simulation training; internship and residency; obstetrics and gynecology department hospital; health human resource training; patient safety